2020
DOI: 10.1097/gox.0000000000002782
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Muscle Reinnervation following Breast Surgery: A Novel Technique

Abstract: Summary: Post-mastectomy pain syndrome is a prevalent chronic pain condition that affects numerous patients following breast surgery. The mechanism of this pain has been proposed to be neurogenic in nature. As such, we propose a novel surgical method for the prophylactic management of postsurgical breast pain: targeted muscle reinnervation of the breast. This article serves to review the relevant current literature of post-mastectomy pain syndrome and targeted muscle reinnervation, describe our current surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…9 A p-value of ≤0.05 indicated significantly heterogeneous studies. The median and interquartile range were used when the mean and standard deviation were not available (Valerio et al 10 ; TMR and standard treatment groups and O'Brien et al 11 ; standard treatment group). As data were not retrieved from the authors, means and standard deviations they were estimated using the method proposed by Wan et al 12…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…9 A p-value of ≤0.05 indicated significantly heterogeneous studies. The median and interquartile range were used when the mean and standard deviation were not available (Valerio et al 10 ; TMR and standard treatment groups and O'Brien et al 11 ; standard treatment group). As data were not retrieved from the authors, means and standard deviations they were estimated using the method proposed by Wan et al 12…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…If nerves are encountered that cannot be used for reinnervation because they are too proximal or distal, or if they have been transected in error at the level of the chest wall, our preference is to perform either targeted muscle reinnervation (TMR) or regenerative peripheral nerve interface reconstruction (RPNI) with the nerve endings to decrease the risk of chronic pain and possibly phantom sensations. 14 , 15 TMR is a technique in which the proximal nerve end is coapted to a small muscle motor branch in close proximity to the nerve stump. 16 RPNI is a technique in which the nerve stump is wrapped in a small muscle cuff.…”
Section: Targeted Nac Reinnervation: Coaptation At the Chest Wallmentioning
confidence: 99%
“…On the premise of ensuring the complete removal of the focus during the operation, it is recommended to protect the skin, residual breast tissue, lymphoid tissue and nerve tissue as much as possible to avoid damage. A study has shown that complete resection of the injured intercostal nerve can also reduce the occurrence of neuroma and postoperative pain [102].…”
Section: Pain Preventionmentioning
confidence: 99%